2016
DOI: 10.17305/bjbms.2016.738
|View full text |Cite
|
Sign up to set email alerts
|

Remifentanil-induced preconditioning has cross-talk with A1 and A2B adenosine receptors in ischemic-reperfused rat heart

Abstract: The purpose of this study was to determine whether there is a cross-talk between opioid receptors (OPRs) and adenosine receptors (ADRs) in remifentanil preconditioning (R-Pre) and, if so, to investigate the types of ADRs involved in the cross-talk. Isolated rat hearts received 30 min of regional ischemia followed by 2 hr of reperfusion. OPR and ADR antagonists were perfused from 10 min before R-Pre until the end of R-Pre. The heart rate, left ventricular developed pressure (LVDP),velocity of contraction (+dP/d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Various studies have documented the functional and physical interaction between adenosine and opioid receptors. Indeed, there is a cross-talk between these receptors in inducing cardioprotective effects [ 50 51 52 ]. It has been documented that adenosine may activate opioid receptors to induce cardioprotection during preconditioning [ 22 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have documented the functional and physical interaction between adenosine and opioid receptors. Indeed, there is a cross-talk between these receptors in inducing cardioprotective effects [ 50 51 52 ]. It has been documented that adenosine may activate opioid receptors to induce cardioprotection during preconditioning [ 22 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al described that there is a cross-talk between opioid and adenosine receptors in remifentanil preconditioning-induced cardioprotection. The authors demonstrated that the protective effects of remifentanil were abolished by antagonists of opioid, A 1 and A 2B receptors suggesting the interrelationship between opioids and adenosine [ 50 ]. An earlier study also described the interaction between spinal mu-opioid receptors and adenosine in remote conditioning [ 51 ].…”
Section: Mechanisms Involved In Adenosine Preconditioningmentioning
confidence: 99%
“…18 Finally, sufentanil was used in both groups; opioids produce cardioprotection against ischemia-reperfusion injury in rodents in a manner potentially related to adenosine receptor cross-talk. 19 Future studies should address these important points in order to better inform the utility of different anesthetic preconditioning regimens in cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The potential cross talk between adenosine and opioid receptors in the heart has been shown by various groups of researchers. 83 -85 Peart and Gross revealed that adenosine and opioids elicit cardioprotective effects via cross talk between these respective receptors. The authors demonstrated that morphine-induced cardioprotective effects against sustained ischemia–reperfusion in rat model of myocardial infarction were abolished in the presence of selective A 1 receptor blocker, DPCPX.…”
Section: Relationship Of Opioids With Adenosine and Other Mediators Imentioning
confidence: 99%
“…This indicates that there might be an existence of potential cross talk between opioid and adenosine receptors during remifentanil preconditioning, and adenosine A 1 and A 2B receptors are likely involved in mediating the cardioprotective effects of opioids. 85…”
Section: Relationship Of Opioids With Adenosine and Other Mediators Imentioning
confidence: 99%